Analisis Pertimbangan Hakim Mengenai Keadaan Meringankan Hukuman Pada Putusan MA Nomor 813k/Pid/2023 Berdasarkan Asas Proporsionalitas Pemidanaan - Helda Okta Havifah; Somawijaya Somawijaya; Rully Herdita Ramadhani (Jurnal Hukum dan Sosial Politik, 2024)
This research aims to analyze the judge's considerations regarding the circumstances of mitigating the sentence in the Supreme Court decision Number 813k/Pid/2023 based on the principle of proportionality of punishment. The principle of proportionality of punishment is a principle of criminal law which demands that the punishment given must be proportional to the error committed by the convict. The research method used is a literature study by collecting and analyzing data from relevant Supreme Court decisions as well as theoretical reviews related to the principle of proportionality of punishment. The research results show that the judge's consideration of Inspector General Ferdy Sambo's service as a member of the National Police as a mitigating circumstance was appropriate. Although theoretically, a person's service should not be used as a reason to mitigate punishment, in practice, the service of a defendant is often considered in court decisions in Indonesia. However, the judge's consideration of merit as a reason for mitigating punishment in this case was not sufficient to reduce the reproach attached to the defendant, especially with his state apparatus status. Therefore, the decision of the panel of judges to change the sentence to life imprisonment was wrong and not in accordance with the principle of proportionality